Penelope Voyages : Women and Travel in the British Literary Tradition - Lawrence, Karen R. (Reading women writing., 2018)
Looking at travel writing by British women from the seventeenth century on, Karen R. Lawrence asks an intriguing question: What happens when, instead of waiting patiently for Odysseus, Penelope voyages and records her journey-when the woman who is expected to waitsets forth herself and traces an itinerary of her own?Lawrence ranges widely, discussing both fiction and nonfiction and traversing the genres of travel letters, realistic and sentimental novels, ethnography, fantasy, and postmodern narrative. In examining works as dissimilar as Margaret Cavendish's rendition of the Renaissance adventure narrative and Christine Brooke-Rose's postmodernist Between, she explores not only the significance of gender for travel writing, but also the value of travel itself for testing the limits of women's social freedoms and restraints.Lawrence shows how writings by Frances Burney, Mary Wollstonecraft, Sarah Lee, Mary Kingsley, Virginia Woolf, and Brigid Brophy reconceive the meanings of femininity in relation to such apparent oppositions as travel/home, other/self, and foreign/domestic. Despite the differences-historical, generic, political-among these writers, Lawrence maintains, they share common insights. Their accounts overturn the dichotomy between adventure and domesticity, demonstrating something illusory within both the stability of home and the freedom of travel.